2010
DOI: 10.1371/journal.pone.0013653
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Liver Stage-Specific Promoter Region of the Malaria Parasite Plasmodium

Abstract: During the blood meal of a Plasmodium-infected mosquito, 10 to 100 parasites are inoculated into the skin and a proportion of these migrate via the bloodstream to the liver where they infect hepatocytes. The Plasmodium liver stage, despite its clinical silence, represents a highly promising target for antimalarial drug and vaccine approaches. Successfully invaded parasites undergo a massive proliferation in hepatocytes, producing thousands of merozoites that are transported into a blood vessel to infect red bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 27 publications
3
44
0
Order By: Relevance
“…These studies also determined that LISP2, named after its expression pattern comparable with LISP1 (Tarun et al, 2008), is exclusively expressed in the mid-to-late liver stages stages. Another group has independently confirmed these results by characterizing stage-specific expression using the promoter region of P. berghei LISP2, in conjunction with a dual luminescence system (Helm et al, 2010; De Niz et al, 2015). Immunofluorescence assays of liver stages showed that LISP2 is transported to the vacuolar space and then, after processing, exported into the hepatocyte cytoplasm (Orito et al, 2013; Itani et al, 2014).…”
Section: 6-cys Proteins In the Pre-erythrocytic Stagesmentioning
confidence: 87%
“…These studies also determined that LISP2, named after its expression pattern comparable with LISP1 (Tarun et al, 2008), is exclusively expressed in the mid-to-late liver stages stages. Another group has independently confirmed these results by characterizing stage-specific expression using the promoter region of P. berghei LISP2, in conjunction with a dual luminescence system (Helm et al, 2010; De Niz et al, 2015). Immunofluorescence assays of liver stages showed that LISP2 is transported to the vacuolar space and then, after processing, exported into the hepatocyte cytoplasm (Orito et al, 2013; Itani et al, 2014).…”
Section: 6-cys Proteins In the Pre-erythrocytic Stagesmentioning
confidence: 87%
“…Stable transgene integration into the dispensable S1 (sporozoite expressed gene 1) locus of P. yoelii , which enables fluorescence expression throughout the parasite life cycle, has overcome the possibility of reversion by plasmid excision and also eliminated survival disadvantages associated with transgene expression in the small ribosomal subunit locus, a strategy previously utilized for both P. berghei and P. yoelii [32, 78]. The recent construction of powerful P. berghei strains such as luciferase-GFP, mCherry, tdTomato as well as novel GFP-expressing strains with improved brightness [79-83], in particular if used in combination with the wide range of transgenic or full knockout C57Bl/6 mice, which are more susceptible to P. berghei , should compensate for the higher levels of liver inflammation and the lower rates of LS maturation previously associated with this parasite.…”
Section: Imaging the Elusive Plasmodium Liver Stagementioning
confidence: 99%
“…The observed time course of PbMAPK1 subcellular localization was found to be independent of the integrity of the DFG motif putatively involved in ATP positioning (and thus kinase activity) (PbMAPK1(D178A)), integrity of the putative activation motif (PbMAPK1(T198A/Y200A)) and the presence of a putative coiled-coil domain in the kinase’s C-terminal domain (PbMAPK1-Δcc) ( Figure 2 and Figure S2 ). The observed localizations were identical for parasite lines expressing PbMAPK1 N-terminally and C-terminally fused to GFP and independent of the promoter (constitutive EEF1alpha promoter or liver stage-specific promoter [17]) used to control the expression of the fusion protein ( Figure 2 ). Expression of the full-length PbMAPK1-GFP fusion protein was confirmed by western blot analysis of mixed blood stage parasites ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 65%
“…Waters). Constructs for liver stage-specific expression were produced using the plasmid pGFP 103464 [17], a pL0017-based vector in which the constitutive EEF1alpha promoter has been replaced by a liver stage-specific promoter. Plasmids were linearized with ApaI and SacII and used for transfection of P. berghei blood stage schizonts as described by Janse et al [54].…”
Section: Methodsmentioning
confidence: 99%